Comparison the Efectiveness of Autogenic Relaxation and Deep Breath Relaxation on Fatigue Value in Renal Failure Patients During Hemodyalisis - Indhit Tri Utami; Tri Kesuma Dewi; Sri Nurhayati; Fitri Annisa (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Fatigue is one of the problems with a fairly high prevalence among the effects of hemodialysis which hurt the quality of life. Fatigue can be done with relaxation. Relaxation can be done with autogenic and deep breath relaxation. Objectives: This study aims to compare the effectiveness of Autogenic Relaxation and Deep Breathing Relaxation on the Fatigue Value of Chronic Kidney Failure Patients Undergoing Hemodialysis. Methods: This study used a quasi-experimental two-group randomized pre-post test design. The sample in this study amounted to 40 respondents in total sampling. Bivariate analysis using independent t-test. Results: The results showed that there was no difference in the results between autogenic relaxation and deep breathing relaxation. Conclusion: Autogenic relaxation and deep breathing relaxation are equally effective in reducing fatigue in renal failure patients undergoing hemodialysis.